Daily exposure to either a high‐ or low‐energy‐dense snack food reduces its reinforcing value in adolescents. Issue 2 (7th January 2017) - Temple, Jennifer L.; Van der Kloet, Erika; Atkins, Amanda M.; Crandall, Amanda K.; Ziegler, Amanda M.
Abstract : Objective: To examine the impact of daily exposure to a low‐energy‐dense (LED) or a high‐energy‐dense (HED) snack food on its reinforcing value (RRV) in adolescents with healthy weight, overweight, or obesity. Methods: A parallel‐group, randomized trial was used to assess RRV of LED or HED snack food at baseline and again after exposure to that snack food daily for 2 weeks in 77 adolescents, aged 13 to 17 years. Information on eating‐related subject characteristics was also collected at baseline. Results: After 2 weeks of daily exposure, the RRV of the snack foods was significantly reduced in all participants, regardless of energy density or participant weight status. Among individuals who were high in dietary restraint only, those randomized to LED food found their snack food less reinforcing at baseline than those who were randomized to HED food. Baseline eating‐related variables also differed as a function of weight status. Conclusions: Daily exposure to snack food in adolescents reduces the RRV of that food regardless of snack food energy density or weight status of the adolescent. This finding differs from adults, suggesting that increases in RRV of HED food after repeated exposure may develop after adolescence.